Pengaruh Inflasi Dan Bi Rate Terhadap Indeks Harga Saham Gabungan (IHSG) Pada Perusahaan Di BEI - Zaki, Zaki (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of Inflation and Bi Rate on the Composite Stock Price Index on the Indonesia Stock Exchange. Taking this title is based on economic phenomena that have occurred in recent years, the occurrence of covid-19 is the main factor in the ups and downs of the Indonesian economy, this is the basis for researching the effect of inflation and exchange rates on the composite stock price index on the Indonesian stock exchange. This research uses quantitative research. The data taken in this study includes the entire Composite Stock Price Index listed on the Indonesia Stock Exchange from January 2017 to December 2021. The data is referred to as Time Series data. With the results of the study, it is stated that the results of the tests that have been carried out prove that inflation has no effect on the stock price index with sig 0.120 > 0.05, the Bi Rate has a significant effect on the joint stock price index with sig 0.000 < 0.05 and simultaneously inflation and exchange rates effect on the composite stock price index with sig 0.000 <0.05. With a coefficient of determination of 0.423, this shows that inflation and the Bi Rate can predict information about the composite stock price index of 42.3%, the rest is influenced by other variables.